Gender Differences in Competitiveness and Risk Taking: Comparing Children in Colombia and Sweden (2011)
We explore gender differences in preferences for competition and risk among children aged 9-12 in Colombia and Sweden, two countries differing in gender equality according to macro indices. We include four types of tasks that vary in gender stereotyping when looking at competitiveness: running, skipping rope, math and word search. We find that boys and girls are equally competitive in all tasks and all measures in Colombia. Unlike the consistent results in Colombia, the results in Sweden are mixed, with some indication of girls being more competitive than boys in some tasks in terms of performance change, whereas boys are more likely to choose to compete in general. Boys in both countries are more risk taking than girls, with a smaller gender gap in Sweden.